Ludwig’s Angina: The Original Angina - Karim Kassam; Ashraf Messiha; Manolis Heliotis (Case Reports in Surgery)
Ludwig’s angina was first detailed by the German surgeon Wilhelm Friedrich von Ludwig in 1836. We present a case which needed awake fibreoptic intubation due to severe trismus and a prolonged period intubated in the Intensive Care Unit after incision and drainage of neck spaces and removal of his lower wisdom teeth. He was finally discharged a week after admission and followed up in the outpatient clinic. The case is presented with clinical photographs and a video of the fibreoptic intubation to illustrate the airway.